Energy Efficiency Assessment of Electric Bicycles - Tomasz Matyja; Zbigniew Stanik; Andrzej Kubik (Energies, 2025)
Electric-assist bicycles have recently become very popular. However, riding them generally requires significantly more energy, generated simultaneously by the motor and the rider, compared to much lighter traditional bicycles. Assessing the energy efficiency of electric-assist bicycles in comparison to traditional bikes allows us to determine in which cases using electric bikes is cost-effective and in which it is not. This study proposes a method for evaluating the energy efficiency of bicycles, which stands out by relying on relatively imprecise data recorded at low frequency by a commercial bike computer with accessories. The core of the method is an algorithm developed by the authors to determine the tractive force acting on the bicycle and rider, based on a minimal set of recorded data: road incline, riding speed, and the wind speed component parallel to the direction of movement. Depending on the situation, the tractive force may act as a driving force or as a braking force. Based on the calculated tractive force, the power required to maintain the recorded bicycle speed can be estimated.